Management strategies in mango orchards and their effect on soil quality and productivity in Los Cajones, Michoacán - Ordaz Gallegos, Jordan; Rodríguez, María de las Nieves; García Cúe, José Luis; Pimentel Equihua, José Luis (Revista Mexicana de Ciencias Agrícolas, 2020)
The different management systems and diversity of species in the orchards influence soil fertility and consequently crop productivity, for this reason the objective of the research was to assess fertility, soil quality and biodiversity management under three different mango production systems. The present study was carried out in the town of Los Cajones, Michoacán, in three mango orchards. The first evaluation was made up of a guide that integrated items of soil quality and biodiversity management applied to producers. The second evaluation was made by laboratory analysis of the soils of each orchard. The results of soil quality and biodiversity management indicate that the organic management system obtained the best values, as a result of the practices and structure of the orchard, while the orchard under conventional management presented the lowest values in both indicators. However, organo-mineral management obtained the best results in laboratory analyzes for the variables organic carbon (2.68%), organic matter (4.66%), nitrogen (1.59%), phosphorus (16.48 g kg-1) and exchange capacity. cationic (29.18 cmol+ kg-1), followed by organic management. Organo-mineral fertilization promotes a better availability of nutrients to be used by the crop, in addition to reducing the amount of chemical inputs, promoting rational use.
Keywords: organic; organo-mineral; production systems